Changes in Job Instability and Insecurity Using Monthly Survey Data - Gottschalk, Peter; Moffitt, Robert (Journal of Labor Economics, 1999)
This article provides evidence on changes in short‐term job instability and insecurity using the Survey of Income and Program Participation. Monthly measures from this data set are contrasted with annual measures from the Survey of Income and Program Participation and the Panel Study of Income Dynamics. Neither data set shows an increase in job turnover during the 1980s and 1990s. We also examine indicators of increased insecurity. These include the probability that a job ends involuntarily, is followed by a spell of nonemployment, or that the subsequent job has lower wages. These indicators of insecurity also show no upward trend.